“It’s not a waste of time!” Academics’ views on the role and function of academic reading: A thematic analysis - Miller, Kirsty; Merdian, Hannah (Journal of University Teaching and Learning Practice, 2020)
The role of academic writing in the development of academic literacy in university students has been considered in some depth in the literature. However, the view of lecturers as to the role and value of academic reading is notably less explored and warrants further exploration. Academic staff from a broad range of subject areas were invited to participate in a survey on the role and function of academic reading. Using an explorative approach, the study investigated academics’ views about reading behaviour with regards to the students’ academic journey, their own academic development, and its incorporation into their teaching. All comments were thematically analysed, resulting in a number of elicited themes and subthemes. The paper highlighted the key role of academics in the modelling, rewarding, and teaching of academic reading and discusses practical implications for Higher Education, particularly with regards to academic teaching and students’ skills development.